Prevalence of depression and the use of antidepressants among Iraqi medical students - Usama Kadem Radi; Ali Hamid Abdul-Hussein; Uday Abdul-Reda Hussein (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background:Health, as defined by the World Health Organization (WHO), is "a state of complete physical, mental, and social well-being and not merely the absence of disease or infirmity." Objective: This research aims to explore the frequency of depression among medical students in Iraq Design: This is a cross-sectional study with the participation of Iraqi medical students (n=1725) conducted in Iraq medical population using a multi-item questionnaire over 6 months (From March 2024 – September 2024). Beck's Depression Inventory was used as a tool for gathering the responses of the participants. Results: The results of the study showed the superiority of women over men in having depression Women constituted 65.9% (n = 866) of those with depressive symptoms compared to 56.4% (n = 232) of those without depression. The most prevalent antidepressant was Fluoxetine (37.9%) followed by Sertraline (27.6%) and Escitalopram (22.4%). In general the results revealed the increased prevalence of depression among Iraqi medical students. Conclusion: Depression is a major mental health issue for future doctors in Iraq. Many students report a variety of symptoms, including sorrow, worry, weariness, difficulty in concentration, and lack of enthusiasm, suggesting that depression is common among this demographic. More research is needed to understand the complex processes that lead to depression in this demographic, but some studies have identified potential risk factors.